Global powers in the 21st century [ strategies and relations - Kozlowski, Amand , 1985-; Lennon, Alexander T. J. , 1969- (A Washington quarterly reader, 2008)
Experts analyze the changing perspectives and objectives of global powers China, Japan, Russia, India, and the European Union in a strategic landscape shaped by the Iraq War